A preliminary study on problem based learning and its implementation in architectural education - Abdullah, Fadzidah; Mohd. Yaman, Maheran (Common Ground Publishing Pty Ltd, 2008)
This paper explores Problem Based Learning (PBL) educational approach and investigates a case study where PBL was implemented in architectural education. It aims to evaluate the appropriateness of Problem Based Learning for the pedagogical improvement and development of architectural education. A preliminary exploration of PBL is essential to understand what the educational approach could offer in improving architectural education. It is found that PBL has been recognised as an innovative educational approach and shown to have the potential to enhance the education process and its outcomes. Many discipline of tertiary education such as engineering, medicine, management, and law, have adopted the educational approach since it was introduced in Medical Faculty of McMaster University, Canada, in the late 1960ï¿½s. However, implementation of PBL in architectural education is limited within two (2) schools of architecture only: in Technical University of Delft (TUDelft), the Netherlands, and in University of New Castle, Australia. Further investigation on methods of PBL implementation in TUDelft is carried out to evaluate PBL implementation in architectural education. It is hope that this investigation provides basis to other schools of architecture on what direction architectural education should go in improving the pedagogy of architectural education as a whole.